Role of primary and secondary prevention in atopic dermatitis - Oszukowska, Magdalena; Michalak, Iwonna; Gutfreund, Katarzyna; Bienias, Wojciech; Matych, Marta; Szewczyk, Anna; Kaszuba, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Atopic dermatitis (AD) is a serious epidemiological problem in industrialized countries. The incidence of AD has increased considerably over the last 30 years. Atopic dermatitis is a chronic, recurrent, inflammatory skin disease accompanied by strong itching. It is characterized by typical features depending on age. The parents of children suffering from AD must be prepared to change their lifestyle. They should avoid factors which can promote skin lesions and apply appropriate, regular skin care. The article describes primary prevention of AD as well as prophylactic measures to avoid skin eczema. It presents the role of infections, vaccinations, breastfeeding and the influence of domestic animals, house renovation and moulds on development of AD. The article also describes the significance of the epidermal barrier, skin colonization by microbial agents, pruritus, stress, food and inhalant allergy among people who suffer from AD.